ANALISIS KEBUTUHAN AIR IRGASI UNTUK PERTANIAN DI DESA SAMPE KECAMATAN RHEE - Bayu Septian Erfandi; Eti Kurniati; Totok Hari Dewanto (Hexagon Jurnal Teknik dan Sains, 2021)
Sampe Village is a village located in Rhee Subdistrict, Sumbawa Besar Regency, with an area of 35 Ha / m² where the research was conducted. The large number of people, the majority of whom are farmers, make water needs increasing, so the role of agricultural irrigation is very important to meet the water needs of farmers. However, there are still many farmers who do not maintain irrigation channels in this area. Based on the survey conducted, there were several channels that were damaged intentionally or unintentionally. The need for water in the irrigation area in the last two years had experienced a shortage of irrigation water, namely in 2017 and 2018 where the water demand was not fulfilled after the second period of planting. Therefore, we need an analysis of the distribution of the distribution of the fastest water supply that does not affect or reduce the need for irrigation water so that it is sufficient until after the second planting and planning of channel dimensions at several points that are damaged. Calculation of irrigation water needs is done using the standard method of irrigation planning. Where the crop pattern used is rice-maize which is viewed from the local farmers' habits. The net field water requirement for rice (Net Field Reuerement) is calculated as determined by the Directorate General of Irrigation (1986). To plan the dimensions of the channel, the 1980 irrigation technical planning criteria guidebook was used, which was sourced from the journal Effendy (Irrigation canal design). From the results of the investigation conducted, it was found that the calculation of irrigation water needs was 19.07 mm / day in December at the time of land preparation and the smallest was in March at 3.70 mm / day. With a system of continuous irrigation water patterns during the growing season. For the planning of the channel dimensions, two channel models are used, namely a trapezoidal shape with a width of = 0.50 m and a height of 0.50 m, and the second form, a square with a size of 0.50 m width and 0.30 m height.